Rancang Bangun Sistem Informasi Geografis Pemetaan Mahasiswa UNISBA Blitar menggunakan React JS dan Mapbox - Ahsan, Muhammad Fahmi; Lestanti, Sri; Puspitasari, Wahyu Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
The Islamic University of Balitar (Unisba) in the City and Regency of Blitar plays a vital role in education and community development. Since its establishment in 2003, Unisba has rapidly grown, now encompassing eight faculties and 18 accredited study programs. However, managing and visualizing student distribution data remains a challenge. This research aims to design and develop a Geographic Information System (GIS) for mapping Unisba students using ReactJS and Mapbox with an Agile development model. This approach is expected to assist campus management in analyzing student distribution data for more effective promotional strategies. System testing was conducted using black-box and closed beta testing methods to ensure the reliability and usability of the system. Black-box testing yielded a result of 95.8%, while expert IT testing scored 74%, categorized as